APLICATION OF ACYBENZOLAR-S-METHYL ON COTTON CROP TO CONTROL OF Aphis gossypii (GLOVER) AND Ramularia areola (ATKINSON) - Mamore Martins, Gustavo Luis; Tomquelski, Germison Vital; Papa, Geraldo [UNESP] (Univ Estadual Mato Grosso Sul, 2015)
Acibenzolar-S-methyl acts as an activator of natural plant defenses, inducing plant resistance against pests and diseases. The objective of this study was to evaluate the activity of acybenzolar-S-methyl on Aphis gossypii (Glover) and Ramularia areola (Atkinson) in the cotton crop. The experiment was conducted in Selviria (MS). The experimental design was randomized blocks with plots in a factorial (2x6), constituted by the combination of two cotton cultivars (Acala-90 and DeltaOpal) and six treatments of resistance. The treatments were: 1) control, 2) acybenzolar-s-methyl (20 g i.a. ha(-1)), 3) acybenzolar-S-methyl + azoxystrobin (20 + 40 g i.a ha(-1)), 4) acybenzolar-s-methyl + thiophanate methyl (20 + 350 g i.a. ha(-1)), 5) azoxystrobin (40 g i.a. ha-1) and 6) thiophanate methyl (350 g i.a. ha(-1)). Aphis gossypii was evaluated with an interval of 10 days after the application of treatments. The severity of R. areola at 101, 109 and 116 days after emergence was analyzed in ten plants marked in the plot. The results show that applying acybenzolar-smethyl, alone or in combination with fungicides, the rates of 20 g i.a. ha(-1) reduced the population of A. gossypii. The acybenzolar-S-methyl (20 g i.a. ha-1) provided the lowest incidence of R. areola.
Keywords: Gossypium hirsutum; aphid; ramularia; resistance inducer